THE CORRELATION OF OCCUPATIONAL STRESS WITH SUBJECTIVE FATIGUE WOMEN WORKERS IN WEAVING LOOM UNIT PT. X - Andarini, Yulia Dwi; Eka Prasetya, Tofan Agung (Faculty of Vocational Studies, Universitas Airlangga, 2017)
Background: An occupation with a high risk of work fatigue is an occupation in textile industry. The involvement of women in the textile industry sector in Indonesia is dominant. Women labors who run work on domestic and public sector will be less inclined a work fatigue. Subjective fatigue is the problem faced by women workers at production division weaving loom unit of PT. X. Purpose: This study aimed to determine occupational stress correlation with subjective fatigue in weaving loom unit PT. X. Method: Type of this observational analytic study was using a cross sectional design. The number of research subject were 95 people. An occupational stress is independent variable. The dependent variable is a subjective fatigue. Occupational stress measurement was using job stress indicator questionnaire. Subjective fatigue measurement was using Subjective Self Rating Test questionnaires. Chi square test used as significance test. All test used 95% confidence interval and significance level of p=0,05. Result: Chi square test result showed that occupational stress has significant association with subjective fatigue. Conclusion: An occupational stress has a positive correlation with subjective fatigue women workers in weaving loom unit PT. X.